An introduction to fire dynamics - Drysdale, Dougal (Chichester, West Sussex : Wiley, 2011)
"A new edition of the leading introduction to the science of fire phenomena, complete with the latest research, data and additional problemsThis book is unique in that it identifies fire science and fire dynamics and provides the scientific background necessary to the development of fire safety engineering as a professional discipline. It is essential reading for all involved in the field from fire safety engineering students to fire prevention officers. After 21 years as a bestseller, Dougal Drysdale's classic introduction has been brought up-to-date with the latest data and research in a third edition. Features numerical problems with answers illustrating the quantitative applications of the concepts presented. Includes quantitative experimental data regarding material properties. Successfully course-tested at Massachusetts' Worcester Polytechnic Institute and the University of Edinburgh, and widely adopted throughout the world. Of relevance to those working in building design, fire physics and chemistry. "--
"This book is unique in that it identifies fire science and fire dynamics and provides the scientific background necessary to the development of fire safety engineering as a professional discipline"--
Includes bibliographical references and index.
Keywords: Fire; Flame